PENGARUH PERSEPSI KEADILAN PADA KEPUASAN PEMULIHAN DAN NIAT KONSUMEN BERPERILAKU DALAM KONTEKS KEGAGALAN LAYANAN: Studi Eksperimen Terhadap Konsumen Pengadu dan Bukan-Pengadu - , Jeanne Ellyawati ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study examines the model of consumer perceptions of service recovery in the context of service failure. Adopting the concept of justice theory, this study is to investigate the influence of perceived justice and its impact on recovery satisfaction. Furthermore, the study evaluates the influence of recovery satisfaction on word of mouth communication, purchase intention and the intention to switch. The data used in this study were collected based on laboratory experimental design. The 381 graduate students were recruited as participants. Hypothesis testing was employed by ANOVA, regression and SEM. The results of empirical studies suggest that both non-complainers as well as complainers perceive the highest interactional justice than those of distributive and procedural justice. Good communication with the consumers in the service failure episodes can turn the unsatisfied customer to become satisfied, although compensation and procedure are perceived injustice. Initiative service recovery from service provider increase perceived justice positively. The three-dimension of perceived justice partially as well as simultaneously effect on recovery satisfaction positively. Furthermore, recovery satisfaction effects positively on word of mouth and repurchase intentions, but negatively on intention to switch. The finding is that intention to switch has a dual role in this model. Besides as a consequence of the relationship on recovery satisfaction, it mediates the relationship between recovery satisfaction and word of mouth intention. It is also mediates the relationship between recovery satisfaction and repurchase intention. This can be interpreted that unsatisfied customer who intent to switch to other brand, also tends to decrease spreading positive word of mouth communication and repurchase intention.